Induction of transient tenogenic phenotype of high-density cultured human dermal fibroblasts. (August 2015) - Wang, Wenbo; He, Aijuan; Zhang, Zhiyong; Zhang, Wenjie; Zhou, Guangdong; Cao, Yilin; Liu, Wei
Abstract Previous study showed that high-density culture supported phenotype maintenance of in vitro expanded tenocytes. This study explored the possibility of inducing the tenogenic phenotype of dermal fibroblasts by high-density monolayer culture. Human fibroblasts were seeded either in high-density (2.5 × 106 per 10 cm dish) or at low-density (0.36 × 106 per 10 cm dish). A preliminary tenogenic phenotype was observed in high-density cultured cells after one passage with significantly enhanced tenogenic gene expression. With continued cultivation to passage 3, scleraxis (SCX), tenomodulin (TNMD), collagen I, III, VI, decorin and tenascin-c were all significantly upregulated in high-density cultured dermal fibroblasts as opposed to low-density cells. High-density culture also led to relatively elongated cell shape, whereas cells appeared in spread shape in low-density culture. In addition, cytochalasin D treatment disrupted the cellular cytoskeleton and resulted in inhibition of density-induced tenogenic gene expression. However, high-density cultured fibroblasts failed to induce other lineage differentiations (osteogenic, chondrogenic and adipogenic). It also failed to induce tenogenic phenotype in high-density cultured chondrocytes. Mechanism studies revealed enhanced gene expression of growth and differentiation factors (GDF) 5, 6, 7 and 8 and transforming growth factor-β (TGF-β)1 in the high-density group and enhanced protein production of both GDF8 and TGF-β1. Moreover, BMP/GDF signaling inhibitor (LDN193189) and TGF-β signaling inhibitor (LY2109761) could both abrogate the density induced phenotype. In conclusion, high-density culture was able to induce transient tenogenic phenotype of dermal fibroblasts likely via cell morphology change and production of pro-tenogenic factors.